you have to use the QE formula
x=[16+/-rt(256-204)]/2
=[-16+/-rt52)]/2
=[-16+/-2rt13)]/2
=[2{-8+/-rt13}]/2
=-8+/-rt13
2006-10-25 16:35:47
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
When you can't directly factor, use the quadratic formula
x = (16+/-â(256-204))/2
x = (16+/-2â(13))/2 = 8+/-â(13)
So the factored form would be
(x-8-â(13))*(x-8+â(13))
2006-10-25 23:35:51
·
answer #2
·
answered by just♪wondering 7
·
0⤊
0⤋
people like to use the formula so much O_o
however I think in this case completing the square is much easier
x^2 - 16x + 51
= x^2 - 16x + 64 - 13
= (x-8)^2 - (sqrt13)^2
then we know A^2 - B^2 factors to (A-B)(A+B)
thus
= (x-8-sqrt13) (x-8+sqrt13)
2006-10-25 23:55:26
·
answer #3
·
answered by kb27787 2
·
0⤊
0⤋
The factors are:
(x - 8 + â13) (x - 8 - â13);
2006-10-25 23:39:25
·
answer #4
·
answered by Pascal 7
·
0⤊
0⤋
x^2 - 16x + 51
x = (-b ± sqrt(b^2 - 4ac))/(2a)
x = (-(-16) ± sqrt((-16)^2 - 4(1)(51)))/(2(1))
x = (16 ± sqrt(256 - 204))/2
x = (16 ± sqrt(52))/2
x = (16 ± sqrt(4 * 13))/2
x = (16 ± 2sqrt(13))/2
x = 8 ± sqrt(13)
this problem can't be perfectly factored, but if you were to, it would look like
(x - (8 + sqrt(13)))*(x - (8 - sqrt(13)))
2006-10-25 23:48:38
·
answer #5
·
answered by Sherman81 6
·
0⤊
0⤋
i just used the quadratic solution for x, where x = (-b plus/minus sqrt(b^2 - 4ac))/2a
we equate the solution to zero and then we get the factors.. :)
we get the factors
[x - 8 + sqrt(13)]
[x - 8 - sqrt(13)]
try this.. it works!
2006-10-25 23:38:39
·
answer #6
·
answered by Jeremy 2
·
0⤊
0⤋